Genetic variability of mitochondrial DNA of Vultur gryphus (Andean Condor) in Cusco and Apurimac from molting feathers - Quispe Montoya, Ramón Gustavo (2021)
The intrapopulation genetic variability of Vultur gryphus (Andean condors) from Cusco and Apurimac regions was evaluated by amplification and sequencing of mitochondrial DNA corresponding to the control region and 12S ribosomal subunit (D-Loop-RNAr12S), Cytochrome Oxidase subunit I (COI) genes and NADH dehydrogenase subunit II (ND2) gene. DNA was extracted from the calamus of feathers recollected from captive and wild specimens. The main indices of genetic diversity such as the haplotype diversity, the nucleotide diversity, the average number of nucleotide differences and the number of polymorphic sites were analyzed. The PCR amplification success rate was 100% for the three mitochondrial amplified sequences. Four haplotypes were identified from the 600 bp sequenced of D-Loop-RNAr12S region; six haplotypes from the 704 bp sequenced of the COI gene; five haplotypes from the 1090 bp sequenced of the ND2 gene. The COI gene presented the highest haplotype diversity (Hd = 0.468), the D-Loop-RNAr12S region presented the highest index of nucleotide diversity (π = 0.00086), while the COI gene presented the highest average number of nucleotide differences (K = 0.52615). The results show low levels of genetic variability in the mitochondrial genes of the Andean Condor in the study area, indicating a population with a homogeneous genetic structure.